The Effect of Pre-milking Stimulation on Teat Morphological Parameters and Milk Traits in the Italian Water Buffalo - Costa, Angela; De Marchi, Massimo; Visentin, Giulio; Campagna, Maria Concetta; Borghese, Antonio; Boselli, Carlo (Frontiers in Veterinary Science, 2020)
Water buffaloes (Bubalus bubalis) are very sensitive to environmental stimulus before and during milking and this explains why disrupted milk ejections due to blood oxytocin level instability are frequent in this specie. According to the literature, the manual stimulation (MS) of teats before milking promotes oxytocin release and allows milk ejection to start within 2 - 3 minutes. However, the pre-milking stimulation of teats is not always part of the milking routine in Italian buffalo farms; moreover, buffaloes with unstable milk let down are sometimes treated with exogenous oxytocin (OX). Different types of pre-milking stimulation can impact differently on the mammary gland epithelium and structures and therefore on milk yield. In this study, we observed the changes in the teat morphological traits before and after application of 3 types of stimuli, i.e. no manual stimulation (NS), MS, and OX, in buffaloes reared in an Italian dairy farm. In particular, measurements were available for 23 and 21 buffaloes for front and rear teats, respectively. Subsequently, the effect of the pre-milking stimulation type was estimated on teat morphological characteristics and on milk traits recorded after the application of stimuli. Results showed that teat canal length was shorter (P < 0.05) after stimulation in the case of MS and OX compared to NS. Cistern diameter was overall greater for MS and lower for OX. On the contrary, teat wall thickness was greater and lower for OX and MS, respectively. Milk yield and quality (fat, protein and somatic cell score) were similar across the 3 types of pre-milking stimulation. In perspective, the impact of these types of pre-milking stimulation should be evaluated on a large scale and the focus might be put on mammary gland epithelium integrity, mastitis incidence, and other udder health indicators in milk, e.g. electrical conductivity, differential somatic cell count, lactose content and sodium and chloride concentration.